2014
DOI: 10.1590/abd1806-4841.20142613
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNFα therapy in the management of psoriasis: experience of a state referral center

Abstract: BACKGROUNDPsoriasis is a chronic immune-mediated disease, characterized by increased levels of TNFα. Anti-TNFα agents have revolutionized the treatment of severe psoriasis by targeting an important molecule involved in its pathogenesis.OBJECTIVESWe report the experience of a state referral center that uses anti-TNFα agents for psoriasis.METHODSWe conducted a retrospective case series. Seventy-four out of 120 patients met the inclusion criteria. Clinical and laboratory data was analyzed using the chi-squared, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Another case series at a state referral centre in Brazil included 74 psoriatic patients treated with anti‐TNF alpha. It found that 95.9% of patients had been treated with traditional therapies before the administration of biologics . Forty‐nine individuals (66.2%) were treated simultaneously with methotrexate, in doses ranging from 10 to 15 mg/week.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another case series at a state referral centre in Brazil included 74 psoriatic patients treated with anti‐TNF alpha. It found that 95.9% of patients had been treated with traditional therapies before the administration of biologics . Forty‐nine individuals (66.2%) were treated simultaneously with methotrexate, in doses ranging from 10 to 15 mg/week.…”
Section: Resultsmentioning
confidence: 99%
“…It found that 95.9% of patients had been treated with traditional therapies before the administration of biologics. 32 Forty-nine individuals (66.2%) were treated simultaneously with methotrexate, in doses ranging from 10 to 15 mg/week. The main reason for therapy with biologics was an insufficient response to standard therapies (55.4%).…”
Section: Treatment Patternmentioning
confidence: 99%
“…The available studies that focused on comorbidities are listed in Table 2 . Silva et al 7 evaluated the profile of psoriasis patients using biological drugs. The main indications for biological therapy were a poor response to other systemic treatments (55.4%) and a psoriatic arthritis diagnosis (81.1%).…”
Section: Epidemiology and Comorbidities Of Psoriasis In Brazilian Patmentioning
confidence: 99%